Human Rights in the Shadow of Colonial Violence : The Wars of Independence in Kenya and Algeria - Klose, Fabian (Book collections on Project MUSE., 2013)
This book explores the relationship between the human rights movement emerging after 1945 and the increasing violence of decolonization. Based on material previously inaccessible in the archives of the International Committee of the Red Cross and the United Nations Human Rights Commission, this comparative study uses the Mau Mau War (1952-1956) and the Algerian War (1954-1962) to examine the policies of two major imperial powers, Britain and France. The author considers the significance of declared states of emergency, counterinsurgency strategy, and the significance of humanitarian international law in both conflicts. The author's findings from these previously confidential archives reveal the escalating violence and oppressive tactics used by the British and French military during these anticolonial conflicts in North and East Africa, where Western powers that promoted human rights in other areas of the world were opposed to the growing global acceptance of freedom, equality, self-determination, and other postwar ideals. Practices such as collective punishment, torture, and extrajudicial killings did lasting damage to international human rights efforts until the end of decolonization. This book demonstrates the mutually impacting histories of international human rights and decolonization, expanding our understanding of political violence in human rights discourse.